Peningkatan Hasil Belajar Siswa dengan Menggunakan Model Kooperatif Tipe Scramble Berbantuan Media Question Card - Wawan Kurniawan Purnomo Aji; Sulistyowati Sulistyowati; Istiyati Mahmudah (Universitas Maritim AMNI Semarang, 2025)
This study aims to (1) Describe the implementation of Indonesian language learning using the Scramble type cooperative model assisted by Question Card Media in Class IV. (2) Know and analyze the improvement of student learning outcomes by using the Scramble type cooperative model assisted by Question Card Media in Indonesian language learning. This study used a Classroom Action Research (PTK) approach which was carried out in two cycles. Each cycle includes four stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class IV B MIS Miftahul Huda 2 Kota Palangka Raya with a total of 27 students. Research data were collected through learning outcome tests, teacher and student activity observations. Data analysis was carried out quantitatively descriptive to determine changes in learning outcomes as well as improving teacher and student activities during learning. The results showed (1) In cycle I, the analysis of teacher activity in managing the class obtained a percentage of 82.5% with very good criteria. As for the implementation in cycle II, the analysis of teacher activities managing the class became 85% with very good criteria, which means that in this case there was an increase. While student activity in cycle I got a percentage of 82.1% with very good criteria and an increase in cycle II with a percentage of 91% with very good criteria. (2) Student learning outcomes using the scramble type coopearification model assisted by Question Card media had a positive impact on improving student learning outcomes in cycle I the percentage of student completeness reached 51.8% while in cycle II it increased by 92.5%. In cycle 1, the N-Gain test obtained a medium category with a value of 0.3384 with the N-Gain score division category of 0.3 ≤ g ≤ 0.7. While in cycle 2 get a high category of 0.7117 with the N-Gain score division category g> 0.7.